Effects of cerebellar transcranial alternating current stimulation in cerebellar ataxia: study protocol for a randomised controlled trial - Liu, Xia; Lin, Wei; Zhang, Lin; Zhang, Wan-Li; Cheng, Xiao-Ping; Lian, Yan-Hua; Li, Meng-Cheng; Wang, Shi-Zhong; Chen, Xin-Yuan; Gan, Shi-Rui (Frontiers in Neuroscience, 2023)
Background: Cerebellar ataxia (CA) is a movement disorder that can affect balance and gait, limb movement, oculomotor control, and cognition. Multiple system atrophy-cerebellar type (MSA-C) and spinocerebellar ataxia type 3 (SCA3) are the most common forms of CA, for which no effective treatment is currently available. Transcranial alternating current stimulation (tACS) is a non-invasive method of brain stimulation supposed to alter cortical excitability and brain electrical activity, modulating functional connectivity within the brain. The tACS can modulate the cerebellar outflow and cerebellum-linked behaviour and it is a proven safe technique for humans. Therefore, the aim of this study is to 1) examine whether cerebellar tACS improves ataxia severity and various non-motor symptoms in a homogeneous cohort of CA patients consisting of MSA-C and SCA3;2) explore the time course of these effects, and 3) assess the safety and tolerance of cerebellar tACS in all participants. Methods/design: This is a 2-week, triple-blind, randomised, placebo-controlled study. 164 patients (MSA-C: 84, SCA3: 80) will be recruited and randomly assigned to either active tACS or sham tACS, in a 1:1 ratio. Patients, investigators, and outcome assessors are unaware of treatment allocation. Cerebellar tACS (40min, 2mA, ramp-up and down periods of 10s each) will be delivered over ten sessions, distributed in two groups of five consecutive days with a two-day break in between. Outcomes are assessed after the tenth stimulation (T1), and after one month (T2) and three months (T3). The primary outcome measure is the difference between the active and sham groups in the proportion of patients with an improvement of 1.5 points in SARA score after 2 weeks of treatment. In addition, effects on a variety of non-motor symptoms, quality of life, and autonomic nerve dysfunctions are assessed via relative scales. Gait imbalance, dysarthria, and finger dexterity are objectively valued via relative tools. Finally, functional magnetic resonance imaging is performed to explore the possible mechanism of treatment effects. Discussion: The results of this study will inform whether repeated sessions of active tACS benefit CA patients and whether this form of non-invasive stimulation might be a novel therapeutic approach to consider in a neuro-rehabilitation setting.